Impact analysis of the thermal mechanical coupling characteristics of graphite morphologies during laser cladding of gray cast iron. (1st May 2017) - Yi, Peng; Liu, Yancong; Fan, Changfeng; Zhan, Xianghua; Xu, Pengyun; Liu, Tuo
Abstract: Cladding and numerical experiments on thermodynamic coupling were conducted to determine the thermal response features and microcracks of graphite and environment phases during surface laser cladding of gray cast iron. A micromodel of graphite–environment phase was established using numerical methods. On the basis of this model, a quantitative analysis on the thermal mechanical coupling characteristics of microstructures was realized, the relationship with microcracks at tip of graphite was established, and the influence of morphological difference on local stress concentration was obtained. Results showed considerable stress concentration at the tip of graphite during cooling stage, and on the whole, the stress concentration at both ends of graphite was in direct proportion to the length of the graphite. Moreover, sufficiently short graphite resulted in further increase in stress concentration. The influence caused by tip angle was more considerable than that of length, and sharpness was in direct proportion to stress concentration. For stress fields at both ends of dimer graphite, collinear distribution easily caused stress concentration, and more obvious stress concentration was observed when the two tips were closer. The interactive effect was weak and the influence on stress concentration was minimal when two graphite pieces were in parallel or vertical distribution. Highlights: Cladding experiment and numerical experiment on thermodynamic coupling are carried out. Different micro model of graphite-environment phase is established. The relationship between thermal stress and micro cracks at tip of graphite are studied. Influencing rule of morphological difference on local stress concentration is obtained.